Perancangan Interior Gedung Pernikahan dengan Konsep Budaya Tionghoa - Theodore, Alvin (Intra, 2015)
Interior design wedding venue with Chinese cultureconcept is a masterpiece of design that is designed as analternative for Chinese people to be married with the maximumChinese culture. In this scheme, there is a blessing room providedin the area of design, so that the bride and groom canto be morepractical to get married. The differences in this wedding hall withthe other is in its value - the value of Chinese wedding philosophyin it. Thus the room becomes more meaningful and bringsblessings for the bride.The design is in accordance with the era development, which isnow often applying modern style. Therefore, the application ofform and character of the room will tend to modern but did notleave the hallmark of the character of Chinese culture weddingprocession in it. Such as lotus, phoenix and dragon, numbers thatrepresents luck for Chinese people, also the Chinese weddingprocess itself are being implemented into the design elements.This design will focus on the value / meaning of each space andindirectly to the cultural conservation of Chinese wedding tomeet the needs of people who wants to get married under theChinese culture.